THE ANALYSIS OF TEACHING VOCABULARY TO EFL THROUGH READING TESTS OF COLLEGE STUDENTS IN JAKARTA - ferdias prihatna sari (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2023)
Teaching vocabulary in the English as a foreign language (EFL) context is challenging. Incidental vocabulary learning is limited due to a lack of second language (L2) input, and most words are learned through classroom instruction. Overall, research has shown marginal L2 vocabulary growth in many EFL situations. Such research indicates a need for a more effective and ef?cient approach to teaching vocabulary in the EFL context. This chapter discusses how to optimise vocabulary learning in the EFL context. It touches on the following questions: Which words should be taught? How should vocabulary be taught? How many words do EFL learners need to know? What should a vocabulary-learning programme include? How can vocabulary learning be fostered given limited classroom time? Which activities might be useful in indirect vocabulary learning?.